2003
DOI: 10.2337/diacare.26.1.193
|View full text |Cite|
|
Sign up to set email alerts
|

Determinants of Fetal Growth at Different Periods of Pregnancies Complicated by Gestational Diabetes Mellitus or Impaired Glucose Tolerance

Abstract: OBJECTIVE -To determine maternal parameters with the strongest influence on fetal growth in different periods of pregnancies complicated by an abnormal glucose tolerance test (GTT).RESEARCH DESIGN AND METHODS -Retrospective study of 368 women with gestational diabetes mellitus (GDM; Ն2 abnormal GTT values, n ϭ 280) and impaired glucose tolerance (IGT; one abnormal value, n ϭ 88) with 869 ultrasound examinations at entry to and during diabetic care. Both groups were managed comparably. Abdominal circumference (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

13
54
1
7

Year Published

2004
2004
2015
2015

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 103 publications
(75 citation statements)
references
References 24 publications
13
54
1
7
Order By: Relevance
“…33,34 However, in our study maternal GDM status did not predict LGA infants nor high %BF. 35 This may be attributed to the tight glycaemic control previously reported in our maternal population mitigating the effects of maternal hyperglycaemia on the fetus.…”
Section: Main Findingscontrasting
confidence: 83%
“…33,34 However, in our study maternal GDM status did not predict LGA infants nor high %BF. 35 This may be attributed to the tight glycaemic control previously reported in our maternal population mitigating the effects of maternal hyperglycaemia on the fetus.…”
Section: Main Findingscontrasting
confidence: 83%
“…30) and a previous history of macrosomia were the only early predictors of large-for-gestational age infants among women with impaired glucose tolerance in pregnancy (30). From gestational week 28 fasting glucose level was also an independent predictor.…”
Section: Discussionmentioning
confidence: 88%
“…Although earlier studies have not LGA was defined as birthweight ≥90th centile, and SGA as birthweight <10th centile, according to Scottish birthweight standards (by fetal sex, parity and gestational age) [24] HbA 1c was reported to be a significant predictor of LGA birthweight in a cohort of women with type 1, type 2 and gestational diabetes after adjustment for a number of confounders [30]. In a study of pregnancies complicated by gestational diabetes or impaired glucose tolerance, maternal fasting glycaemia during 32-35 weeks was the strongest predictor of accelerated growth in the late third trimester, whereas in the late second and early third trimester and at birth the dominant predictors were previous LGA or maternal obesity [29]. The Hyperglycaemia and Adverse Pregnancy Outcome (HAPO) study reported that mild antenatal maternal hyperglycaemia in women without known diabetes is also associated with an increased risk of LGA [28].…”
Section: Discussionmentioning
confidence: 99%